The Effectiveness of SMART Technique Group Counseling in Reducing Peer Pressure Among Campus Organization Students - Mutia Fitri; Saiful Akhyar Lubis (MASI Mandiri Edukasi, 2025)
Students are in a developmental phase that is full of challenges, both academically and socially-psychologically. Peer pressure is one of the dominant factors influencing students' decision-making, especially in campus organisation participation. Many students join organisations not out of personal interest but rather due to social pressure to be accepted in their environment. This study aims to examine the effectiveness of group counselling using the SMART (Specific, Measurable, Achievable, Relevant, Time-bound) technique in reducing peer pressure while also increasing students' interest in organising. The research method uses a quantitative approach with a One-Group pretest-posttest design experimental setup. The study subjects consisted of six third-semester students from BKPI-2 UINSU who were identified as having high levels of peer pressure. The research instruments used were the Peer Pressure Scale and the Organisational Participation Interest Scale, which have been validated and are reliable. The intervention was carried out through six sessions of SMART-based group counselling. The analysis results using a paired sample t-test showed a significant decrease in peer pressure from high to low (p < 0.05) and a significant increase in organisational interest from low to high (p < 0.05), with a very large effect size. These findings prove that the SMART technique of group counselling effectively reduces social pressure and enhances students' intrinsic motivation. This research has implications for developing counselling services in higher education, particularly in helping students make more independent social decisions that align with their personal goals